Rising Global Fears of Foreign Interference in Higher Education - Long, Kyle; Etheridge, Chief; O’Connell, Carly; Hugins, Kat (International Higher Education, 2021)
This article recognizes growing concern worldwide about the exploitation of higher education actors and institutions by foreign entities for malign purposes. It examines how higher education has become increasingly vulnerable to interference from geopolitical adversaries. The authors highlight recent allegations of espionage, propaganda, and strategic meddling in higher education in various countries before analyzing the validity and implications of these claims. They conclude by proposing solutions to counter undue foreign influence.